Methodology review: a protocol to audit the representation of female athletes in sports science and sports medicine research - Smith, E. S.; McKay, A. K.; Ackerman, K. E.; Harris, R.; Elliott-Sale, K. J.; Stellingwerff, T.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
Female-specific research on sports science and sports medicine (SSSM) fails to mirror the increase in participation and popularity of women`s sport. Females have historically been excluded from SSSM research, particularly because their physiological intricacy necessitates more complex study designs, longer research times, and additional costs. Consequently, most SSSM practices are based on research with men, despite potential problems in translation to females due to sexual dimorphism in biological and phenotypical parameters as well as differences in event characteristics (e.g., race distances/durations). Recognition that erroneous extrapolations may hamper the efforts of females to maximize their athletic potential has created an impetus to acknowledge and readdress the sex disparity in SSSM research. To direct the priorities for future research, it is prudent to first develop a comprehensive understanding of the gaps in current knowledge by systematically "auditing" the literature. By conducting audits of the literature to highlight underdeveloped topics or identify potential problems with the quality of research, this information can then be used to expediently direct new research activities. This paper therefore presents a standardized audit methodology to establish the representation of female athletes in subdisciplines of existing SSSM research, including a template for reporting the results of key metrics. This standardized audit process will enable comparisons over time and between research subdisciplines. This working guide provides an important step toward achieving sex equity across SSSM research, with the eventual goal of providing evidence-based recommendations specific to the female athlete.